Changes in Bulk and Rhizosphere Soil Microbial Diversity and Composition Along an Age Gradient of Chinese Fir (Cunninghamia lanceolate) Plantations in Subtropical China - Wang, Yuzhe; Jiao, Pengyu; Guo, Wen; Du, Dajun; Hu, Yalin; Tan, Xiang; Liu, Xian (Frontiers in Microbiology, 2022)
Soil microorganisms play key roles in biogeochemical cycling in forest ecosystems. However, whether the responses of microbial community with stand development differed in rhizosphere and bulk soils remains unknown. We collected rhizosphere and bulk soil in Chinese fir plantations with different stand ages (7a, 15a, 24a and 34a) in subtropical China, and determined bacterial and fungal community variation via high-throughput sequencing. The results showed that soil bacterial but not fungal community diversity were significantly differed among stand ages and between rhizosphere and bulk soils (P < 0.05). The differences of Shannon-Wiener and Simpson’s indices between rhizosphere and bulk soil varied with stand age, with significant higher soil bacterial diversity in rhizosphere than bulk soils in 7a and 34a plantations (P < 0.05), but no significant differences of soil bacterial diversity between rhizosphere and bulk soils in 15a and 24a plantations (P > 0.05). Soil microbial community composition varied significantly with stand age but not between the rhizosphere and bulk soil. The dominant bacterial phyla at all ages were Acidobacteria and Proteobacteria while the dominant fungal phyla were Ascomycota and Basidiomycota in both rhizosphere and bulk soil. They showed inconsistent distribution patterns along stand age gradient (7-34a) in the rhizosphere and bulk soil, suggesting distinct ecological strategy (r-strategist vs. k-strategist) of different microbial taxa, as well as changes in the microenvironment (i.e. nutrient stoichiometry, root exudates). Moreover, bacterial and fungal community composition in rhizosphere and bulk soil were governed by distinct driving factors. TP and NH4+-N are the two most important factors regulating bacterial and fungal community structure in rhizosphere soil, while pH and NO3--N, DON and TN were driving factors for bacterial and fungal community structure in bulk soil, respectively. Collectively, our results demonstrated that the changes in microbial diversity and composition were more obvious along stand age gradients than between sampling locations (rhizosphere vs bulk soil) in Chinese fir plantations, and the ecosystem harbored diverse microbial taxa with different nutrient preferences and metabolic characteristics.